Isolasi, Identifikasi, dan Uji Efektivitas Metabolit Sekunder Bakteri Endofit Sembung (Blumea balsamifera) Sebagai Biopestisida Terhadap Kutu Kebul (Bemisia tabaci) - Radina I. Timumun; Harista Agustina; Ani M. Hasan; Wirnangsi D. Uno; Yuliana Retnowati (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
Blumea balsamifera contains bioactive metabolites that are presumed to support the presence of endophytic bacteria capable of producing secondary metabolites with pesticidal potential, making this plant a promising source of eco-friendly biopesticides. This study aimed to isolate and identify endophytic bacteria associated with B. balsamifera and to evaluate the insecticidal activity of their secondary metabolites against Bemisia tabaci. Endophytic bacteria were isolated using the Direct Planting and Grinding methods, followed by purification, Gram staining, and metabolite production through liquid culture in Luria-Bertani (LB) medium. The isolated strain was identified as a Gram-negative, short rod-shaped bacterium producing a yellowish supernatant, which was successfully extracted using ethyl acetate to obtain an extracellular metabolite fraction. Toxicity bioassays revealed a clear dose–response pattern, with 24-hour mortality of B. tabaci increasing from 55.00% at 35% concentration to 80.00% at 75% concentration. Probit analysis yielded an LC₅₀ value of 1500.95, while LT₅₀ decreased significantly from 42.26 hours to 15.87 hours as metabolite concentration increased. These findings confirm that endophytic bacteria isolated from B. balsamifera are capable of producing secondary metabolites effective in suppressing B. tabaci populations, highlighting their strong potential for development as environmentally friendly plant-based biopesticides.